Competition and the railroads: A European perspective - Günter Knieps (Albert-Ludwigs-Universität Freiburg, Institut für Verkehrswissenschaft und Regionalpolitik, 2012)
The reform of European railroads is a time-consuming process strongly charac-terized by its path-dependency. Firstly, a short outline of the historical roots of the controversial debates on the role of the state and the markets, and the organi-zation of competition in European railroad industries is provided. Secondly, the opening of the market for train services in the context of the liberalization of European transport markets since 1985 is characterized and the regulatory pre-conditions for competition on the tracks are presented. Thirdly, the evolution of track access regulation in Europe during the last decades is analyzed, differenti-ating between the period of negotiated third party access since 1991, the intro-duction of ex ante regulation by the first railroad infrastructure package in 2001, and the danger of overregulation posed by the recent Draft Directive of July 2012 establishing a single European railway area. Fourthly, the role of competi-tion on the markets for rail services and the reform process of interoperability requirements are considered. Finally, competition on the markets for rail ser-vices and public subsidies for rail infrastructures as well as subsidies for train services are evaluated.
Keywords: 330